Stability of the Two-Link Metrobus - Sakhno, Volodymyr; Polyakov, Viktor; Murovany, Igor; Sharai, Svitlana; Lyashuk, Oleg; Plekan, Uliana; Tson, Oleg; Sokol, Mariana (Communications - Scientific Letters of the University of Zilina, 2023)
It has been shown that a perspective type of passenger transport is a metro bus, which can be both two- and three-link. Mathematical model of an autotrain has been developed for a two-link metrobus with both an uncontrolled and a controlled trailer, with the help of which it is established that the speed of the metro bus is 10 m/s, the angular speed of links racking, lateral acceleration, the angles of axle wheels' diversion while manoeuvring of ``steering wheel jerk'' ``Shift'' and ``turn'' have a fading nature of oscillation, which ensures the stability of its motion. At the same time, the value of lateral accelerations in the center of masses of metrobus separate links with an uncontrolled trailer at a speed of 15 m/s, while performing various manoeuvres do not exceed 0.45 g, according to this characteristics, such metrobus is stable, instead of a metrobus with a controlled trailer, which at this speed loses its stability. This should be considered when developing the advanced two-link metrobus of increased overall length (24 m).
Keywords: metrobus; trailer; controlling wheel module; angular velocity; lateral acceleration; uncontrolled and controlled autotrain trailer